The Costs of Online Learning: Examining Differences in Motivation and Academic Outcomes in Online and Face-to-Face Community College Developmental Mathematics Courses - Francis, Michelle K.; Wormington, Stephanie V.; Hulleman, Chris (Frontiers in Psychology, 2019)
Although online courses are becoming increasingly popular in higher education, evidence is inconclusive regarding whether online students are likely to be academically successful, and what might account for differences in academic outcomes. In this study, we documented online and face-to-face students’ outcomes in community college mathematics courses, and whether differential outcomes could be explained as a function of students’ motivation or student characteristics (i.e., gender, underrepresented ethnic/racial minority status, first-generation college status, and adult learner status). Over 2,400 developmental mathematics students reported on their math motivation and perceptions of instructors at the beginning (Week 1) and middle (Weeks 3, 5) of the semester. Findings indicated that online students received lower grades, and were less likely to pass and more likely to withdraw from their courses than face-to-face students, with online adult learners receiving particularly low final course grades. In contrast, online and face-to-face students did not differ on incoming motivation or changes in motivation across the semester. Subgroup analyses suggested largely similar patterns of motivation across student characteristics, with two exceptions: (1) underrepresented ethnic/racial minority students in online courses reported lower perceptions of teacher value than majority or face-to-face students; and (2) adult learners in online courses reported marginally smaller increases in perceived cost than traditional-aged or face-to-face students. Finally, changes in motivation did not mediate the relation between course modality and academic outcomes. Together, findings suggest that online and face-to-face students may not differ meaningfully in their motivation, although online adult learners and underrepresented ethnic/racial minority students may display slightly different patterns on select motivation variables. Small but significant differences academic outcomes across modalities (Cohen’s ds = .17-.28) have implications for community college students’ success in online learning environments, particularly for adult learners who are most likely to be faced with competing demands.